Fibroblast Growth Factor 21 Protects Against Atrial Remodeling via Reducing Oxidative Stress - Chen, Miao; Zhong, Jiawei; Wang, Zhen; Xu, Hongfei; Chen, Heng; Sun, Xingang; Lu, Yunlong; Chen, Lu; Xie, Xudong; Zheng, Liangrong (Frontiers in Cardiovascular Medicine, 2021)
Aim: The changes in structural and electrical of atrium, also known as atrial remodeling, are main characteristics of atrial fibrillation (AF). Fibroblast growth factor 21 (Fgf21) is an important endocrine factor which has been showed to play an important role in cardiovascular diseases. However, the effects of Fgf21 on atrial remodeling have not been addressed yet. The purpose of the present study is to evaluate the effects of Fgf21 on atrial remodeling. Methods and results: Adult mice were treated with Ang II, and randomly administrated with or without Fgf21 for 2 weeks. The susceptibility to AF was assessed by electrical stimulation and optical mapping techniques. Here, we found that Fgf21 administration reduced the inducibility of atrial fibrillation/ atrial tachycardia (AF/AT), improved epicardial conduction velocity and shorted action potential duration at 90% (APD90) in mouse atria. Mechanistically, Fgf21 protected against atrial fibrosis and reduced oxidative stress of atria. Consistently, in vitro study also demonstrated that Fgf21 blocked the up-regulation of collagen by Tgf-β in fibroblasts, and reduced tachypacing-induced oxidative stress including ROS, Tgf-β and ox-CaMKII in atrial myocytes. We further found that that Fgf21 decreased oxidative stress by inducing antioxidant genes, such as SOD2 and UCP3. Fgf21 could also attenuate tachypacing-induced myofibril degradation, down-regulation of L-type calcium channel and up-regulation of p-RyR2, which implicated protective effects of Fgf21 on structural and electrical remodeling in the atria. Moreover, Nrf2 was identified as a downstream of Fgf21 and partly mediated Fgf21-induced antioxidant genes expression in atrial myocytes. Conclusion: Fgf21 administration effectively suppressed atrial remodeling by reducing oxidative stress, which provides a novel therapeutic insight for AF.